2017
DOI: 10.1080/10641963.2017.1334794
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and socioeconomic status: A cross-sectional study in Chongqing, China

Abstract: People of different SES indicate different working and living conditions. They also face different risk factors for prehypertension. Lower education and a history of marital status were associated with a higher risk of prehypertension among residents in Chongqing, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…For China, the results of a systematic review in 2014 and a national survey in 2002 both indicated that the prevalence was higher among men than women [4, 17]. In addition, another research in Chongqing Province of China investigating the prevalence of pre-hypertension also implied a similar result [18]. Our result was consistent with the above, also suggesting that men are more likely to suffer hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…For China, the results of a systematic review in 2014 and a national survey in 2002 both indicated that the prevalence was higher among men than women [4, 17]. In addition, another research in Chongqing Province of China investigating the prevalence of pre-hypertension also implied a similar result [18]. Our result was consistent with the above, also suggesting that men are more likely to suffer hypertension.…”
Section: Discussionsupporting
confidence: 88%
“…The impact of social deprivation on patient health has been well documented. Individuals with greater levels of social deprivation are at an increased risk of major diseases including cardiovascular conditions (1-3), diabetes (4), cirrhosis (5), hypertension (6,7), and an increased incidence of trauma (8)(9)(10). Similarly, lower SES has been correlated with a worse prognosis and a greater likelihood of disease progression for a variety of conditions, and a higher rate of surgical complications (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of social deprivation on patient health has been well documented. Individuals with greater levels of social deprivation are at an increased risk of major diseases including cardiovascular conditions (1)(2)(3), diabetes (4), cirrhosis (5), hypertension (6,7), and an increased incidence of trauma (8)(9)(10). Similarly, lower SES has been correlated with a worse prognosis and a greater likelihood of disease progression for a variety of conditions, and a higher rate of surgical complications (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%